Effect of elastic module degradation measurement in different sizes of the nonlinear isotropic–kinematic yield surface on springback prediction - Baara, Wisam Ali Basher; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar; Ismail, Mohd Idris Shah (MDPI, 2019)
Commercial finite element software that uses default hardening model simulation is not able to predict the final shape of sheet metal that changes its dimensions after removing the punch due to residual stress (strain recovery or springback). We aimed to develop a constitutive hardening model to more accurately simulate this final shape. The strain recovery or balancing of residual stress can be determined using the isotropic hardening of the original elastic modulus and the hardening combined with varying degrees of elastic modulus degradation and the size of the yield surfaces. The Chord model was modified with one-yield surfaces. The model was combined with nonlinear isotropic–kinematic hardening models and implemented in Abaqus user-defined material subroutine for constitutive model (UMAT). The Numisheet 2011 benchmark for springback prediction for DP780 high-strength steel sheet was selected to verify the new model, the Chord model, the Quasi Plastic-Elastic (QPE) model, and the default hardening model using Abaqus software. The simulation of U-draw bending from the Numisheet 2011 benchmark was useful for comparing the proposed model with experimental measurements. The results from the simulation of the model showed that the new model more accurately predicts springback than the other models.